PENINGKATAN KEAKTIFAN DAN HASIL BELAJAR SISWA POKOK BAHASAN PENYUSUTAN AKTIVA TETAP DENGAN METODE MENJODOHKAN KOTAK - Winarti, Winarti (Fakultas Ekonomi, Universitas Negeri Semarang, 2013)
The low studentsâ activeness level in the teaching and learning process willinfluence studentsâ achievement. Choosing the varied and appropriate learning methodis very important for the success of teaching and learning process. The purpose of thisstudy was to enhance the studentsâ activeness and studentsâ learning outcomes at thetopic of Fixed Assets Depreciation by using cooperative learning with match boxmethod, especially for students of class XI AK 2 at SMK N 2 Blora. It was a classroomaction research. The methods of the study were observation and evaluation. The resultsof the research showed that match box method can increase studentsâ activeness.Studentsâ activeness was only 71.05% at the beginning and after using the match boxmethod, it rose up to 84.21% and was successful to improve studentsâ learningoutcomes because studentsâ learning completeness rose from 28.95% to 65.79% .